Analysis of shalat gait - Bani Hashim, Ahmad Yusairi; Abu Osman, Noor Azuan; Wan Abas, Wan Abu Bakar; Abdul Latif, Lydia (International Center for Scientific Research and Studies, 2010)
This study was done to analyze the pattern of shalat gait in comparison to walking gait. Force plate system records ground reaction forces when reading walking gait. It produces distinct curves that have profiles of an M-liked shape. This curve exhibits the behaviour of walking gait in term of ground reaction force as a function time. Instead of using force plate system, this work used heuristic method of argument by exploiting the advantages found in graph theory and algebraic representations. The ‘M’ profile was succesfully created using the method proposed. The method was then tested on shalat gait through responses from seventeen subjects who participated in the exercise. At the conclusion of the study it was suspected that shalat routine was similar to walking activity.